(untitled) (Bangladesh Agronomy Journal, 2023)
An experiment was carried out at the Agronomy Research Farm of Sher-e-Bangla Agricultural University, Dhaka during the period from November 2018 to June 2019 to study the nitrogen requirement of boro rice grown with floating duckweed. The experiment was laid out in a Factorial Randomized Complete Block Design with three replications. The treatments were duckweed: viz. D0 = Control (0 g duckweeds m-2), D1 = 200 g duckweeds m-2, D2 = 400 g duckweeds m-2 and D3 = 600 g duckweeds m-2) and nitrogen treatment: N1 = 45 kg N ha-1, N2 = 90 kg N ha-1 and N3 = 180 kg N ha-1). Different doses of duckweeds showed significant influence on most of the parameters of which D2 (400 g duckweeds m-2) treatment the best performance on growth and yield parameters of rice. Among different doses of nitrogen, N2 (90 kg N ha-1) gave the best results on growth and yield parameters of rice. In case of combined effect, D2N2 showed the highest number of tillers hill-1 (16.40), dry weight hill-1 (48.97 g), number of effective tillers hill-1 (14.73) and number of grains panicle-1 (189.50). This treatment combination also showed the highest number of filled grains panicle-1 (183.90), panicle length (25.83 cm), 1000 -grain weight (25.13 g), seed yield (7.24 t ha-1), straw yield (8.47 t ha-1), biological yield (15.71 t ha-1) and harvest index (46.09%). On the other hand, D0N3 gave the least results on these parameters. Findings revealed that application of 400 g duckweeds m-2 with 90 kg N ha-1 showed the superiority over other treatment combinations to produce higher grain yield of boro rice. Bangladesh Agron. J. 2022, 25(2): 109-117